The brainstem-tentorium angle revisited. Difficulties encountered and possible solutions - Laura Joigneau; Yolanda Ruiz; Coral Bravo; Julia Bujan; Miguel A Ortega; Juan De León-Luis (Clinical and Experimental Obstetrics & Gynecology)
Background: Fetal posterior fossa fluid collections (PFFC) can range from normal variants to severe anomalies with highly variable neurological prognosis. The diagnosis of these entities is still a challenge for ultrasound as well as for fetal magnetic resonance imaging (MRI). The measurements of the brainstem-vermis angle (BV angle) and the brainstem-tentorium angle (BT angle) have been described as helpful in the differential diagnosis of the PFFC. Case: We present a case with posterior fossa abnormalities where the measurement of the BT angle could be difficult due to the anatomy distortion. Conclusion: We propose two alternative ways of measuring the BT angle that could be reliable in all the spectrum of PFFC.